Implementation Of OSS-RBA Licensing at the Department of Capital Investment and One-Door Integrated Services, North Minahasa District - Lontoh, Mega; Pangkey, Itje; Dilapanga, Abdul Rahman (JR Education, 2023)
This research examines the effectiveness of the implementation of OSS-RBA UMKM Licensing at the North Minahasa Regency Investment and One-Stop Integrated Services Service (DPMPTSP). The research objectives of this study are 1. To describe, analyze and interpret what is done by the One Stop Integrated Service Investment Service Office in implementing the Online Single Submission Risked Based Approach system in North Minahasa Regency, especially in the process of processing UMKM business permits 2. To describe analyzing and interpreting inhibiting factors in implementing the Online Single Submission Risked Based Approach system at the North Minahasa Regency One Stop Integrated Services Investment Service office in the UMKM business licensing process. The first research focus is on the effectiveness and efficiency of permit services through the OSS System and secondly on supporting factors and inhibiting factors for permit services through the OSS System. This research uses a qualitative approach method. The scope of this research is the investment office and one-stop integrated services in the M district. The research results in this study are that permit services through the OSS system are considered effective and efficient compared to the previous system. Where the OSS system offers innovations that solve existing problems in licensing services. About the OSS system, there are also supporting and inhibiting factors that exist and are related to business permit services. These factors support increased use of the OSS System itself and become inhibiting factors which encourage Regional and Central Governments to provide new strategies or improve the OSS System.